2015
DOI: 10.1111/trf.13274
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and neonatal alloimmune thrombocytopenia: predictive factors of intracranial hemorrhage

Abstract: BACKGROUND In Caucasians, fetal/neonatal alloimmune thrombocytopenia (FNAIT) is most frequently caused by maternal alloimmunization against the human platelet antigen HPA‐1a. The most serious complication of severe FNAIT is intracranial hemorrhage (ICH). ICH mainly occurs in utero; therefore, there is a need to identify noninvasive predictive factors of ICH to facilitate early identification of this condition and to determine response to maternal therapy. STUDY DESIGN AND METHODS We studied gynecologic and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 41 publications
(51 reference statements)
3
49
1
2
Order By: Relevance
“…In the aforementioned Israeli study, Loewenthal et al (2013) suggested that compound heterozygosity for DRB4*01:01 and DRB3*01:01 reduces the success of IVIG treatment based on their finding that only 17% of the infants born to women carrying both alleles achieved platelet counts of over 100 9 10 9 /l, in comparison to 67% of the newborns carrying only DRB3*01:01. Our results, with the corresponding rates of 50% and 8%, respectively, were more in line with a very recent French study (Delbos et al, 2016), but similarly, none of the figures were statistically significant. Finally, although the haplotype HLA-A*01:01-C*07:01-B*08:01-DRB3*01:01-DRB1*03:01-DQA1*05:01-DQB1*02:01 was overrepresented in the confirmed cases, six other haplotypes were also detected in our cohort.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the aforementioned Israeli study, Loewenthal et al (2013) suggested that compound heterozygosity for DRB4*01:01 and DRB3*01:01 reduces the success of IVIG treatment based on their finding that only 17% of the infants born to women carrying both alleles achieved platelet counts of over 100 9 10 9 /l, in comparison to 67% of the newborns carrying only DRB3*01:01. Our results, with the corresponding rates of 50% and 8%, respectively, were more in line with a very recent French study (Delbos et al, 2016), but similarly, none of the figures were statistically significant. Finally, although the haplotype HLA-A*01:01-C*07:01-B*08:01-DRB3*01:01-DRB1*03:01-DQA1*05:01-DQB1*02:01 was overrepresented in the confirmed cases, six other haplotypes were also detected in our cohort.…”
Section: Discussionsupporting
confidence: 81%
“…Only a few studies report an association between the HLA-DRB3*01:01 type and quantitation of the anti-HPA-1a levels (Killie et al, 2008;Bertrand et al, 2011). Recent studies on other allele variants of the HLA-DR family involved in the severity of FNAIT and the responsiveness to IVIG treatment show conflicting results (Loewenthal et al, 2013;Delbos et al, 2016).…”
Section: Fetal and Neonatal Alloimmune Thrombocytopenia (Fnait)mentioning
confidence: 95%
“…The clinical outcome of ICH due to FNAIT is reported to be worse compared to neonatal ICH from other causes75,76 and may be connected to the typical locations of the bleedings in the brain. Severe neurological complications are found in 36%–68% of ICH cases24,26,77,78 and fetal or neonatal death due to ICH is reported in the range of 9%–46%24,57,68,79 when evaluated retrospectively. A large cohort study from the international No Intracranial Hemorrhage (NOICH) registry described 43 cases of ICH caused by FNAIT in depth and found that the majority of bleedings (54%) happened before the third trimester and 67% before 34 gestational weeks 77.…”
Section: Clinical Presentation and Outcomementioning
confidence: 99%
“…In the past literature, the mortality rate of ICH was up to 10% [17] and even more in recent studies [19,25] . ICH has been documented as early as 20 weeks of gestation, and 80% of ICH cases occur before the 30th week [18,19,26] .…”
Section: Introductionmentioning
confidence: 99%
“…A serious consequence of FNAIT is intracerebral haemorrhage (ICH), which has been reported to occur in 20-25% of cases [8,16,17] and may lead to neurological impairment and death [18][19][20][21][22][23][24] . In the past literature, the mortality rate of ICH was up to 10% [17] and even more in recent studies [19,25] . ICH has been documented as early as 20 weeks of gestation, and 80% of ICH cases occur before the 30th week [18,19,26] .…”
Section: Introductionmentioning
confidence: 99%